2014
DOI: 10.1016/j.jhin.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Excess length of stay and mortality due to Clostridium difficile infection: a multi-state modelling approach

Abstract: HA-CDI contributes to patients' expected LOS and risk of mortality. However, when quantifying the health and economic burden of hospital-onset of HA-CDI, the heterogeneity in the impact of HA-CDI should be accounted for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 27 publications
5
33
0
Order By: Relevance
“…Strain types are geographically variable 31 and have been linked to differences in disease severity, particularly among patients with the "epidemic" strain, BI/NAP1/027. 32 As demonstrated in our results and the study from van Kleef et al, 20 CDI severity impacts the magnitude of excess LOS; thus, hospitals that have a greater proportion of CDIs caused by epidemic strains may observe a greater impact of CDI on LOS.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Strain types are geographically variable 31 and have been linked to differences in disease severity, particularly among patients with the "epidemic" strain, BI/NAP1/027. 32 As demonstrated in our results and the study from van Kleef et al, 20 CDI severity impacts the magnitude of excess LOS; thus, hospitals that have a greater proportion of CDIs caused by epidemic strains may observe a greater impact of CDI on LOS.…”
Section: Discussionsupporting
confidence: 72%
“…In their cohort, patients with severe CDI had an excess LOS of 11.6 days (95% CI, 3.6-19.6), whereas patients with mild-tomoderate CDI only stayed an additional 5 days (95% CI, 1.1-9.5). 20 In contrast, Mitchell et al 19 observed that CDI did not significantly contribute to LOS among inpatients 2 years and older at a hospital in Australia (0.9 days, 95% CI, 1.8-3.6). 19 However, both of these studies were conducted at single institutions outside of the United States with relatively small numbers of CDI cases.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations